Determinación del índice de prevalencia de otoacariasis canina mediante diagnóstico de laboratorio por hisopados óticos en el cantón de Huaquillas - Olaya Matute, Jhonatan Jose (2014)
In order to determine the prevalence rate of canine Otoacariasis by laboratory diagnosis of otic swabs in dogs Cantón Huaquillas province de El Oro. Was proceeded to the laboratory diagnosis of 365 cases for which a review was conducted to microscope included the following steps: a dry or soaked in glycerine swab was taken, and the otic material I collect, obtained from the sample placed it on a slide objects making a slight rotation and added a drop of glycerin was placed a covering objects and observed in the microscope at 10 or 40 x thus not determined, or the presence of mites. The results show only 3 positive animals Otodectes cynotis, for a prevalence rate of 0.82%, lower than those reported by different authors in other cities.